(untitled) (Sinología hispánica. China Studies Review, 2024)
In 2021, Professor Alicia Relinque Eleta, the Spanish sinologist, translated Mo Xia Zhuan, which is the first Chinese translation of the Spanish classical novel Don Quijote de la Mancha (1603/1988) back into Spanish. Mo Xia Zhuan (1922/1933) was translated by Lin Shu (1852-1924), a monolingual translator, in collaboration with Cheng Jialin, using the English translation The history of the ingenious gentleman Don Quixote of La Mancha by Peter Anthony Motteux (1663-1718) as the intermediary text. Therefore, during the process of translation, a lot of changes occurred if compared with the original Spanish text. By using the translation of Alicia Relinque (1960- ) as a medium, the cultural encounters behind the texts are displayed to see which cultural elements were “activated” and which were “obscured”. As a pilot study, this research aims to discover and analyze a particular case of back-translation, focusing on the changes of identity and relationships of characters to figure out what alterations have been made and the possible reasons during the process of translation. This study can bring new dimensions to the complicated nature of back-translation in particular and translation in general.